Comparison of Vitamin D Serum Values between Rheumatoid Arthritis and Lupus Populations: An Observational Study - Maryam, Sahebari (Open Rheumatol J, 2018)
BACKGROUND: In recent years, the role of Vitamin D (VitD), as an immunomedulator in autoimmune diseases, has been evaluated in basic science and practice. There is a considerable volume of data on the effect of VitD position in lupus and rheumatoid arthritis exacerbation. OBJECTIVE: This study aims to compare VitD serum values in lupus (SLE) and Rheumatoid Arthritis (RA) in the geographical region of northeastern Iran. METHODS: Lupus and RA Patients were selected with various disease activity levels. All the patients received an equal amount of VitD supplementation and were selected by the same inclusion and exclusion criteria. VitD serum values were measured by a commercial ELISA kit. Data were analyzed in SPSS-15. RESULTS: A total of 148 SLE and 156 RA patients were studied. VitD serum levels were 66.54±41.2 nmol/l in the SLE group and 83.74±46.45 nmol/l in the RA group. Statistical analysis showed that VitD serum levels were lower in lupus patients than RA ones (p=0.006). CONCLUSION: Since VitD deficiency is very common in Iran, physiologic doses of VitD supplementation in patients lead to higher serum levels of VitD. Lower VitD values in lupus patients compared with RA ones may stem from intestinal malabsorption, higher doses of corticosteroid therapy, renal involvement and proteinuria, different polymorphisms of VitD receptors, and more sun protection strategies in lupus patients.